2011
DOI: 10.1155/2011/185083
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Method of Generating Parametric Maps of Patlak Ki without Blood Sampling or Metabolite Correction: A Feasibility Study

Abstract: Currently, kinetic analyses using dynamic positron emission tomography (PET) experience very limited use despite their potential for improving quantitative accuracy in several clinical and research applications. For targeted volume applications, such as radiation treatment planning, treatment monitoring, and cerebral metabolic studies, the key to implementation of these methods is the determination of an arterial input function, which can include time-consuming analysis of blood samples for metabolite correcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Thus, an extended version of the sPatlak model, accepting the possibility of relatively small uptake reversibility, could enhance its accuracy by attributing the observed progressive signal intensity loss to an additional kinetic parameter rate constant: the tracer efflux rate constant. In fact, the theoretically expected K i underestimation, when an irreversible compartment replaces a reversible one, has been also confirmed by a number of clinical dynamic PET studies, thus further suggesting the possibility for underlying FDG uptake reversibility in certain normal organs and tumors (Lammertsma et al 1987, Messa et al 1992, Choi et al 1994, Hasselbalch et al 2001, Graham et al 2002, Wu et al 2003, Sayre et al 2011, Hoh et al 2011). …”
Section: Introductionmentioning
confidence: 82%
“…Thus, an extended version of the sPatlak model, accepting the possibility of relatively small uptake reversibility, could enhance its accuracy by attributing the observed progressive signal intensity loss to an additional kinetic parameter rate constant: the tracer efflux rate constant. In fact, the theoretically expected K i underestimation, when an irreversible compartment replaces a reversible one, has been also confirmed by a number of clinical dynamic PET studies, thus further suggesting the possibility for underlying FDG uptake reversibility in certain normal organs and tumors (Lammertsma et al 1987, Messa et al 1992, Choi et al 1994, Hasselbalch et al 2001, Graham et al 2002, Wu et al 2003, Sayre et al 2011, Hoh et al 2011). …”
Section: Introductionmentioning
confidence: 82%
“…However a considerable number of studies suggest uptake reversibility for a range of tracers, as presented previously (Holden et al 1997, Lodge et al 1999, Karakatsanis et al 2015a). Since the sPatlak model assumes irreversible uptake, it may underestimate K i to compensate for lack of reversibility modeling (Messa et al 1992, Sayre et al 2011, Hoh et al 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Although the sPatlak method is robust and therefore attractive for clinical usage, it does not account for uptake reversibility and therefore it may lead to biased K i estimates (Sayre et al 2011, Hoh et al 2011). In fact a number of studies have reported mild reversibility for normal tissues (Fischman and Alpert 1992, Hawkins et al 1992, Okazumi et al 1992, Choi et al 1994, Nelson et al 1996, Huang et al 2000, Graham et al 2000, Zhuang et al 2001, Iozzo et al 2003, Lin et al 2005, Prytz et al 2006) as well as some oncologic malignancy types, such as hepatocellular carcinoma (HCC) tumors (Messa et al 1992, Torizuka et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…erroneously assumes it is zero, resulting in underestimation of the estimated tracer influx rate parameter K i in regions with non-negligible uptake reversibility [18][19][20][21], with the bias becoming larger for stronger underlying k loss rate constants [16,18,19]. However, this model supports a linear graphical analysis method and, thus, it is very robust to noise.…”
Section: Introductionmentioning
confidence: 99%
“…The FDG tracer kinetics may result in considerable changes of the count and contrast levels in both suspected tumors and their background regions, especially in the early frames, where the rise of the TAC is steep with time [1,11]. In addition, it has been shown that FDG may exhibit in some tumor or normal tissue regions a small, but non-negligible, tracer uptake reversibility, whose net tracer efflux effect can be modeled by the kinetic macro-parameter ( k loss ) or tracer efflux rate constant and is linearly dependent on k 4 kinetic micro-parameter [18][19][20][21]. Tracer uptake reversibility, or k loss , is expected to reduce, though to a relatively small extent, the absorbed or metabolized amount of activity, with the apparent effect on TACs being negligible at early frames but gradually becoming stronger at later time frames or TAC segments [19][20][21].…”
Section: Introductionmentioning
confidence: 99%